A Study on Depression, Anxiety and Stress Among Medical Undergraduate Students of a Women’s Medical College, South India - Mandyam, Sindhu; Deekala, Ravi Sankar; G, Swetha Rao; Guthi, Visweswara Rao; Rosivari, Pravallika Sudharani (National Journal of Community Medicine, 2023)
Background: Mental health of a medical student remains affected throughout training due to long study and working hours, extensive course content, examinations, peer competition, uninspiring environments, sleep deprivation. Objectives of this study is to estimate the proportion of Depression, Anxiety and Stress among Women medical undergraduate students and to determine the association between the Depression, Anxiety, Stress and Socio demographic factors among Women medical undergraduate students. Materials and methods: This were a cross sectional Study conducted among First, second, third and fourth year MBBS students of SVIMS - Sri Padmavathi Medical College for Women, Tirupati, Andhra Pradesh. Medical students who were present and willing to participate voluntarily on the day of data collection were included. Sample size calculated was 375. Information collected was socio-demographic details and Depression Anxiety Stress scale [DASS 42] was used to assess depression, anxiety and stress levels. Results: The present study assessed Depression, Anxiety and Stress among 588 medical undergraduates, by using DASS 42 scale which revealed prevalence of depression was 34.7%, anxiety 44% and stress 30.3% and their association year of study, not satisfied, partially satisfied with own education, less consumption water, less sleeping hours and hours of usage of gadgets. Conclusion: The present study found that prevalence of depression 34.7%, anxiety 44% and stress 30.3% among medical undergraduates. Medical students under strain are either unaware of their situation or reluctant to seek help.